139k views
4 votes
Solve the system of equations. y = -6x + 9 y = -3x + 3

User Wxkly
by
6.2k points

2 Answers

3 votes
Hi there


Let y = -6x + 9 ...... ( 1 )

and y = -3x + 3 ....... ( 2 )


Putting the value of yin equation ( 2 )

-6 x + 9 = -3 x + 3

→ 3 ( -2 x + 3 ) = 3 ( - x + 1 )

→ -2x + x = 1 - 3


→ - x = - 2

→ x = 2

Now putting the value of x in equation ( 1 )

y = - 6 ( 2 ) + 9

y = -12 + 9

y = - 3


Hope it helps you

User David Klempfner
by
6.8k points
3 votes


- 6x + 9 = - 3x + 3 \\ 3x = 6 \\ x = 2

Substitute x = 2 into y = - 6x + 9

y = - 6(2) + 9 \\ y = - 12 + 9 \\ y = - 3

Answer : x = 2, y = - 3

Hope this helps. - M
User Alex Stewart
by
6.1k points